The impact of glycaemic load on cognitive performance: A meta-analysis and guiding principles for future research - Chantelle Gaylor (Neuroscience & Biobehavioral Reviews, 2022)
The effect of breakfast glycaemic load (GL) on cognition was systematically examined. Randomised and non-randomised controlled trials were identified using PubMed, Scopus, and Cochrane Library (up to May 2022). 15 studies involving adults (aged 20 – 80 years) were included. Studies had a low risk, or some concerns, of bias. A random-effects meta-analysis model revealed no effect of GL on cognition up to 119 min post-consumption. However, after 120 min, immediate episodic memory scores were better following a low-GL compared to a high-GL (SMD = 0.16, 95% confidence interval [CI] = −0.00 to 0.32, p = 0.05, I2 = 5%). Subgroup analyses indicated that the benefit was greater in younger adults (<35 years) and those with better GT. A qualitative synthesis of 16 studies involving children and adolescents (aged 5 – 17 years) suggested that a low-GL breakfast may also benefit episodic memory and attention after 120 min. Methodological practises were identified which could explain a failure to detect benefits in some studies. Consequently, guiding principles were developed to optimise future study design.